2023
DOI: 10.1186/s12909-023-04310-4
|View full text |Cite
|
Sign up to set email alerts
|

Teaching module for obesity bias education: incorporating comprehensive competencies and innovative techniques

Abstract: Background The majority of the United States population is overweight or obese, and obesity bias is frequently reported by patients. Obesity bias is associated with adverse health outcomes, even independent of body weight. Primary care residents are often sources of obesity bias towards patients with weight, yet education regarding obesity bias is significantly lacking in most family medicine residency teaching curricula. The aim of this study is to describe an innovative web-based module on ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
2
1
0
Order By: Relevance
“…Pre-and post-intervention levels of knowledge and competence on obesity were analysed through survey measures and all participants reported improvement in their understanding of obesity, and at a 6-month follow up, indicated that participating in the workshop positively affected their confidence when caring for patients who have obesity in clinic [ 14 ]. Similar results were reported by Koran-Scholl et al., who implemented an intervention inclusive of a 15-min ​educational video on patient-centred care for family doctors in the United States [ 15 ]. Participants reported that watching the video increased their comfort in discussing obesity treatment options with their patients [ 15 ].…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Pre-and post-intervention levels of knowledge and competence on obesity were analysed through survey measures and all participants reported improvement in their understanding of obesity, and at a 6-month follow up, indicated that participating in the workshop positively affected their confidence when caring for patients who have obesity in clinic [ 14 ]. Similar results were reported by Koran-Scholl et al., who implemented an intervention inclusive of a 15-min ​educational video on patient-centred care for family doctors in the United States [ 15 ]. Participants reported that watching the video increased their comfort in discussing obesity treatment options with their patients [ 15 ].…”
Section: Introductionsupporting
confidence: 84%
“…Similar results were reported by Koran-Scholl et al., who implemented an intervention inclusive of a 15-min ​educational video on patient-centred care for family doctors in the United States [ 15 ]. Participants reported that watching the video increased their comfort in discussing obesity treatment options with their patients [ 15 ].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation